Homoharringtonine Exerts Anti-tumor Effects in Hepatocellular Carcinoma Through Activation of the Hippo Pathway - Wang, Haina; Wang, Rui; Huang, Dan; Li, Sihan; Gao, Beibei; Kang, Zhijie; Tang, Bo; Xie, Jiajun; Yan, Fanzhi; Liang, Rui; Li, Hua; Yan, Jinsong (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is the most prevalent subtype of liver cancer with a mortality rate of approximately 3~6/100,000 and is the third leading cause of cancer-related death worldwide. Although several small-molecule drugs have been developed for the treatment of HCC, the choice of an agent for patients who require systemic chemotherapy at an advanced stage is still limited. The Hippo pathway is an evolutionarily conserved tumor suppressive pathway commonly dysregulated in HCC, which makes it a promising target for anti-HCC therapies. Homoharringtonine (HHT) is an FDA-approved anti-leukemia drug with proven strong anti-tumor activity in solid tumors. In this study, we found that HHT could significantly inhibit HCC cell growth by suppressing cell proliferation and colony formation. Moreover, HHT repressed cell invasion and migration remarkably. Additionally, HHT induced cell cycle arrest at S phase and promoted apoptosis. Most importantly, we showed that HHT-induced apoptosis was a consequence of the Hippo pathway activation. Consistently, the MST1/2 inhibitor, XMU-MP-1, could restore cell viability and reverse HHT-induced cell apoptosis. Furthermore, in vivo results confirmed the tumor inhibitory effect of HHT. Taken together, our findings suggest that HHT is a potential alternative therapeutic agent for the treatment of HCC.